Implementation of Convergence Action to Accelerate Stunting Reduction in Labuhan Batu Regency, North Sumatra - Teguh Suharto; Asriwati Amirah; Rizki Ichwansyah (PSPP JOURNALS, 2022)
Indonesia has set a target in accordance with the SDGs Program in 2030 in the health sector, namely through efforts to improve nutrition and health quality in combating the prevalence of stunting. The achievement of the SDGs goals must be prepared from now on in cross-sectoral coordination. Over the last 20 years, the handling of the stunting problem has been very slow, globally, the percentage of children whose growth is stunted has decreased by only 0.6% per year since 1999. It is predicted that if this continues, 15 years later it is estimated that 450 million children will experience growth retardation or stunting. The contributing factor is thought to be the lack of cross-sectoral roles in preventing stunting, so it is necessary to strengthen the role through convergence action to accelerate stunting reduction. This research is a descriptive study with a qualitative approach using source triangulation, where researchers get data from different sources using the same technique, namely open and in-depth interview techniques. There were 5 informants involved in this study, namely 2 OPD KB Officers, 1 Provincial PIC, 1 Regency PIC and 1 Nutrition Manager. The instruments used for primary data collection were observation, field documentation and interview guides. The results of the study are the factors that encourage the implementation of convergence actions to accelerate stunting reduction are the government's commitment, as well as the involvement of various parties both from the health and non-health sectors, but still need to be further improved. Lack of awareness related to stunting handling and stunting reduction program management that is not well organized because it only considers that it is only the task of nutrition managers so that there is no synergy with others.